Demorest's Family Magazine - Demorest, William Jennings (New York: W. J. Demorest, 1882)
Demorest's Family Magazine. November 1882. Vol. 19, no. 1. -- Cousin Caleb's Thanksgiving -- The Admiral's Ward -- In the Cave of the Guapacos -- A Rosebud -- Wanderers of the Heavens -- An Old Man -- The Galley Acalephas -- Talks with Women: The After-Math -- The Nondescript -- Winter Resorts in Southern Europe -- Equal Development -- Thanksgiving Day -- Fruits of Italy -- The Poetry of Motion -- Home Art and Home Comfort -- Finishing Touches -- Adam Gordon's Two Wives -- Treasures in Tombs -- Memory's Pictures -- A Doleful Subject -- Chinese Schools -- Two Ways -- The Wearing of Amulets -- O Love, My Love No More! -- How the Craze Spreads -- Leisure Hour -- What Women are Doing -- Fancy Work -- Current Topics -- Kitchen: Apples as Food -- Scientific -- Diamonds of Thought -- Spice Box -- Mirror of Fashions: Review of Fashions -- Illustrated Designs -- Fashionable Millinery -- Winter Stuffs in Silk and Wool -- Our "Portfolio of Fashions" for the Autumn and Winter of 1882-83 -- Hair Dressing -- Our "What to Wear" for the Autumn and Winter of 1882-83 -- Novelties in Lingerie -- What to Wear at the Theater -- Ariel Basque -- Ladies' Street Costumes -- Hungarian Basque -- The New Velvets and Plushes -- Valcour Jacket -- The Winter Cloak -- "What to Wear" -- Is it Hats or Bonnets? -- Artificial Light and its Effect upon Color -- House or Street Costume -- French Novelties for Gifts and Decoration -- Misses' Costumes -- Portfolio of Fashions -- Children's Fashions -- Our Purchasing Bureau -- Ladies' Club
New York Illustrated News
Mme Demorest's Mirror of Fashions
Digitized from original print. Valdosta State University Archives and Special Collections. June 15, 2017.
Keywords: Fashion; Women's History; Social History; Children; Catalogue; Illustrated Periodicals; Magazine; Travel; Needlework; Homemaking; Dressmaking; 1800s; 19th Century